Genetic and economic efficiencies of alternative breeding schemes for improvement of local breeds in low-input production systems: The case of the Farta sheep in Northwest Ethiopia - Abebe, A.S.; Alemayehu, K.; Gizaw, Solomon (2025)
Designing and implementing a sound breeding program is essential for sustainably improving livestock productivity. This study evaluated the efficiencies of three breeding schemes for sustainable genetic improvement of indigenous sheep in low-input production systems. The schemes were one-stage selection at six months (Scheme I) or yearling age (Scheme II) and two-stage selections with the first at six months and the second at the yearling age (Scheme III). Each scheme was assessed with three levels of selection proportions (5%, 10% and 20%) and four flock sizes (600, 1200, 1800 and 2400 breeding ewes). Selection responses were simulated using a deterministic approach employed in the SelAction software. For six-month weight, the annual predicted genetic gains ranged from 0.177 to 0.267 kg (Scheme I) and 0.157 to 0.233 kg (Scheme III). For yearling weight, simulated annual genetic gains were 0.268 to 0.399 kg (Scheme II) and 0.265 to 0.398 kg (Scheme III). The expected annual genetic gains for the number of lambs weaned per ewe bred (NLW) and fertility rate were generally small, but the estimates in Schemes II and III were higher compared to Scheme I. The annual economic responses estimated for Schemes I, II, and III ranged from US$0.393 to 0.591, 0.589 to 0.879 and 0.494 to 0.744, respectively. Notably, Scheme II yielded 34% and 16% higher economic returns than Schemes I and III, respectively. The results also revealed that varying the selection proportion significantly influenced the annual selection response, index accuracy, and inbreeding rate. Increasing the flock size had little effect on the genetic progress but significantly reduced the inbreeding rate. Given its genetic and economic benefits alongside operational feasibility, Scheme II, with a 5% selection proportion and a flock size of 1200 breeding ewes, is appropriate for the genetic improvement of indigenous sheep in low-input systems.